2019
DOI: 10.1101/586727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is there an intrinsic relationship between LFP beta oscillation amplitude and firing rate of individual neurons in monkey motor cortex?

Abstract: Beta oscillations are prominent in motor cortical local field potentials (LFPs), and their relationship to the local neuronal spiking activity has been extensively studied. Many studies have shown that in motor cortex, spikes of individual neurons tend to lock to the phase of LFP beta oscillations. However, there are contradictory results concerning whether there is also an intrinsic relationship between the amplitude of LFP beta oscillations and the firing rate of individual neurons. To resolve this controver… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…To compare beta modulations across different studies, it is important to first understand the underlying relationship between the LFP and neuronal spiking activity. Many studies have shown that sensorimotor LFP beta at least partly reflects local activity, with the spikes of inhibitory interneurons and pyramidal tract neurons locking to the phase of beta (Murthy and Fetz, 1996;Donoghue et al, 1998;Baker et al, 1999;Jackson et al, 2002;Denker et al, 2011;Canolty et al, 2012;Confais et al, 2019). However, whether there is also an intrinsic relationship between the amplitude of beta oscillations and neuronal spike rates has been controversial (Canolty et al, 2012;Rule et al, 2017).…”
Section: Prefrontal-basal-ganglia Beta For Stopping Action and Thoughtmentioning
confidence: 99%
See 2 more Smart Citations
“…To compare beta modulations across different studies, it is important to first understand the underlying relationship between the LFP and neuronal spiking activity. Many studies have shown that sensorimotor LFP beta at least partly reflects local activity, with the spikes of inhibitory interneurons and pyramidal tract neurons locking to the phase of beta (Murthy and Fetz, 1996;Donoghue et al, 1998;Baker et al, 1999;Jackson et al, 2002;Denker et al, 2011;Canolty et al, 2012;Confais et al, 2019). However, whether there is also an intrinsic relationship between the amplitude of beta oscillations and neuronal spike rates has been controversial (Canolty et al, 2012;Rule et al, 2017).…”
Section: Prefrontal-basal-ganglia Beta For Stopping Action and Thoughtmentioning
confidence: 99%
“…However, whether there is also an intrinsic relationship between the amplitude of beta oscillations and neuronal spike rates has been controversial (Canolty et al, 2012;Rule et al, 2017). A recent study resolved this issue (Confais et al, 2019) by showing that spike rates and beta amplitude have no intrinsic correlation, but are both modulated by external factors, such as a behavioral task.…”
Section: Prefrontal-basal-ganglia Beta For Stopping Action and Thoughtmentioning
confidence: 99%
See 1 more Smart Citation